Pengaruh Ukuran Perusahaan dan Struktur Aktiva Terhadap Struktur Modal Pada Perusahaan Sektor Industri Dasar dan Kimia Di Bursa Efek Indonesia - TAMPUBOLON, ARSYAF (Jurnal Mahkota Bisnis (Makbis), 2022)
This study aims to determine the effect of firm size, liquidity and profitability variables on firm value. The population of this study was obtained on 73 companies selected using purposive sampling with certain criteria as many as 33 companies. The type of data used in this study is quantitative data. Source of data in this research is secondary data. Data collection techniques were carried out using documentation techniques and data analysis using multiple linear analysis using the F test and t test at a significant level of 0.5% and the coefficient of determination Adjusted R Square was 10.9%, changes in the capital structure variable (Y) were explained by changes in size company and asset structure while the remaining 89.1% is explained by other variables not included in this study. Partial research results show that asset structure has a significant effect on capital structure, while firm size has no significant effect on capital structure. The results of the study simultaneously show that firm size and asset structure have an effect on capital structure.